Residents’ accessibility to public transportation services in Kota Kinabalu City, Sabah - Saravanan Sundara Sakaran; Harifah Mohd Noor; Rosmiza M. Z. (GEOGRAFIA Online, 2020)
Accessibility is the convenience of getting to a destination that uses multiple modes of transportation. One example of such mode is the public transportation. However, the public transportation is often associated with inefficiencies such as incomplete service routes. This study identifies factors that influence the accessibility of public transportation (public buses) services in Kota Kinabalu city. The study used primary data through direct observation of public buses services on several major routes to the city center. Several interview sessions were held with government agencies and bus operators and a set of survey forms were distributed to 274 respondents through the purposive sampling method. This study uses descriptive analysis such as frequency, percentage and mean values using the Statistical Packages for the Social Sciences (SPSS). The results show that there are several main roads to the city center, where there is no public buses service. The three factors contributing to the buses route services are the bus operators, the demand from resident’s factors and the Local Authority factors. The average mean score indicates that the bus operator factor is the highest factor for overall route services (average mean = 3.01) followed by resident’s factor (average mean = 2.90) and Local Authority factor (average mean = 2.83). These findings help the Local Authorities and some relevant agencies to design and planning a more comprehensive public buses service policy for residents in Kota Kinabalu city.